2022
DOI: 10.3390/app12147061
|View full text |Cite
|
Sign up to set email alerts
|

BMI, Body Image, and Quality of Life—Moderating Role of Physical Activity

Abstract: Body mass index (BMI) and body image (BI) are constructs worth examining in the context of physical activity (PA), and they are both related to quality of life (QoL). PA, BMI, and BI should all be considered as associated parameters, and their effect on QoL should be examined and understood. This study aimed to determine the moderating role of PA in the relationship of BMI and BI with QoL. The sample of examinees consisted of 500 respondents (307 women; aged 39 ± 6 years). A physical activity self-evaluation q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Power was determined based on a 50-meter dash. BMI was calculated using the participant's height and weight ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Power was determined based on a 50-meter dash. BMI was calculated using the participant's height and weight ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Regular PAs are recommended to maintain an optimal level of BMI (between 18.5 and 25 points); PAs with moderate and vigorous intensity are especially useful to slow the decline of BMI with increasing age (Cleven et al, 2023). A moderate association was observed for those adults with a good level of daily PA and the positive influence of this on their BMI, body image, and quality of life being (Milanović et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(10) On the other hand, BMI is an indicator of health (11) and the association with QoL has been studied in detail in previous research. (12,13) Findings of previous studies showed contradictory results for the relationship between BMI and QoL. Although some studies stated that obesity has been associated with reduced QoL, even if the comorbid disease has been taken under control, other studies argue that being overweight has been associated with improved QoL.…”
Section: Introductionmentioning
confidence: 99%